2019
DOI: 10.32615/ps.2019.038
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a GLDH-overexpressing Arabidopsis mutant and its responses to high-light stress

Abstract: Ascorbic acid (AsA) is an important antioxidant protecting plant against environmental stresses. L-galactono-1,4-lactone dehydrogenase (GLDH) is a key enzyme in AsA synthesis pathway. To investigate the roles of AsA in mitigating high light (HL) damage, Arabidopsis GLDH mutants SALK_060087 and SALK_008236 with altered GLDH-expression were screened for homozygotes. No homozygotes were identified from SALK_060087, but most individuals of the SALK_008236 line (GLDH-236OE) were GLDH-overexpressing homozygous mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…This residue has been validated to be irreversibly oxidized by H 2 O 2 , inactivating GLDH [70], and has been suggested to be responsible for regulation of GLDH activity during the early stages of heat stress produced programmed cell death [67,71]. Moreover, Arabidopsis GLDH overexpressing lines accumulated higher ascorbate levels and demonstrated higher chlorophyll fluorescence parameters after exposure to high light for 14 days, which led them to have lower sensitivity to light stress [72].…”
Section: Light Regulation Of Ascorbatementioning
confidence: 99%
“…This residue has been validated to be irreversibly oxidized by H 2 O 2 , inactivating GLDH [70], and has been suggested to be responsible for regulation of GLDH activity during the early stages of heat stress produced programmed cell death [67,71]. Moreover, Arabidopsis GLDH overexpressing lines accumulated higher ascorbate levels and demonstrated higher chlorophyll fluorescence parameters after exposure to high light for 14 days, which led them to have lower sensitivity to light stress [72].…”
Section: Light Regulation Of Ascorbatementioning
confidence: 99%
“…Also, more recently, it was demonstrated that the thale cress homozygous mutant (T-DNA insertion mutant designated GLDH-236OE ), which overexpress the GLDH gene, has a significantly high content of AsA in their leaves than wild-type plants. Also, these GLDH gene-overexpressing mutant plants have more tolerance to high light due to a better capacity to eliminate reactive-oxygen species, absorb extra light, and dissipate the thermal energy ( Zheng et al., 2019 ). Together, these results corroborate that the catalytic activity of the GLDH enzyme is an essential step in the L-galactose pathway for AsA biosynthesis in plants.…”
Section: Enzymes Of the L-galactose Pathway For Asa Biosynthesismentioning
confidence: 99%
“…To determine the changes during AsA biosynthesis and the regeneration process, the activities of key enzymes were determined. GLDH catalyzes the final step of AsA biosynthesis and its activity is positively correlated with AsA content across diverse tissues in a species-specific manner [34,35]. Light plays important roles in the expression of GLDH [36].…”
Section: Eop-hli With a High Blue Light Proportion Increased Asa Accu...mentioning
confidence: 99%